Penanganan Terhadap Stigma Masyarakat tentang Orang Dengan HIV/AIDS (ODHA) di Komunitas - Muhammad Saleh Nuwa; Stefanus Mendes Kiik; Antonius Rino Vanchapo (FORIKES, 2019)
Stigma and discrimination against PLWHA have an impact on the opening of the spread of AIDS. This literature review aims to determine the implementation of handling the community's stigma against people living with HIV / AIDS (PLWHA) in the community. Literature search uses the EBSCO, ScienceDirect, Google Scholar and Proquest databases. In the initial stages of searching for journal articles 20 articles from 2010 to 2018 were used using the keywords